Clostridium Perfringens Enterotoxin C-terminal domain labeled to fluorescent Dyes for in vivo visualization of micro-metastatic chemotherapy-resistant ovarian cancer - Cocco, Emiliano (Int J Cancer, 2015)
Identification of micro-metastatic disease at the time of surgery remains extremely challenging in ovarian cancer patients. We used fluorescence microscopy, an in vivo imaging system and a fluorescence stereo microscope to evaluate fluorescence distribution in claudin-3 and -4 overexpressing ovarian tumors, floating tumor clumps isolated from ascites and healthy organs. To do so, mice harboring chemotherapy-naïve and chemotherapy-resistant human ovarian cancer xenografts or patient-derived xenografts (PDX) were treated with the carboxi-terminal binding domain of the Clostridium Perfringens Enterotoxin (c-CPE) conjugated to FITC (FITC-c-CPE) or the near-infrared (NIR) fluorescent tag IRDye CW800 (CW800-c-CPE) either intraperitoneal (IP) or intravenous (IV). We found tumor fluorescence to plateau at 30 minutes after IP injection of both the FITC-c-CPE and the CW800-c-CPE peptides and to be significantly higher than in healthy organs (p<0.01). After IV injection of CW800-c-CPE, tumor fluorescence plateaued at 6 hours while the most favorable tumor to background fluorescence ratio (TBR) was found at 48 hours in both mouse models. Importantly, fluorescent c-CPE was highly sensitive for the in vivo visualization of peritoneal micro-metastatic tumor implants and the identification of ovarian tumor spheroids floating in malignant ascites that were otherwise not detectable by conventional visual observation. The use of the fluorescent c-CPE peptide may represent a novel and effective optical approach at the time of primary debulking surgery for the real-time detection of micro-metastatic ovarian disease overexpressing the claudin-3 and -4 receptors or the identification of residual disease at the time of interval debulking surgery after neoadjuvant chemotherapy treatment.